Specification for control switches (switching devices, including contactor relays, for control and auxiliary circuits, for voltages up to and including 1000 V a.c. and 1200 V d.c.). Position switches with positive opening operation Part 2-2.20, (31st March 1987) - British Standards Institution,
No abstract available